Low-Intensity Steady Background Noise Enhances Pitch Fusion Across the Ears in Normal-Hearing Listeners - Oh, Yonghee; Lee, Sabrina N. (Frontiers in Psychology, 2021)
Binaural pitch fusion is the perceptual integration of stimuli that evoke different pitches between the ears into a single auditory image. This study was designed to investigate how steady background noise can influence binaural pitch fusion. The binaural fusion ranges, the frequency ranges over which binaural pitch fusion occurred, were measured with three signal-to-noise ratios (+15, +5, and −5dB SNR) of the pink noise and compared with those measured in quiet. The preliminary results show that addition of an appropriate amount of noise can reduce binaural fusion ranges, an effect called stochastic resonance. This finding increases the understanding of how specific noise levels can sharpen binaural pitch fusion in normal hearing individuals. Furthermore, it elicits more pathways for research to explore how this benefit can practically be used to help improve binaural auditory perception.